Analisa Deflectometry Dan Tebal Lapis Tambah Dengan Metode PD T-05-2005-B Pada Perekerasan Lentur - Sihombing, Rivai Morhan; Sebayang, Mardani; Shalahuddin, M (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Structural dysfunction will occur on the road such as cracks after passing the design life that can reduce the safety and comfort to the rider through it. It can be fixed by adding overlay. This research was conducted on road sections of Rangau - Duri Bengkalis Regency Riau Province. The purpose of this study is to calculate the overlay thickness using Pd T-05-2005-B method based on the deflection data obtained by using Benkelman Beam. Other than that is to calculate the resilient modulus and stability of the pavement with pick up first the stations that have good subgrade based the deflectometry have been made. This study generate overlay thickness from 4 cm to 13 cm with the design life of 5 years. While with the design life of 10 years, generated overlay thickness from 4 cm to 13.1 cm. Asphalt resilient modulus values obtained is from 1201.95 to 2403.90 Mpa and the stability value is from 1151.29 kg/0.01 in to 2302.59 kg/0.01 in.Keywords: Overlay thickness, Design Life, Pd T-05-2005-B Method, Deflectometry, Resilient modulus, Stability.